Teaching Takt-Time, Flowline, and Point-to-point Precedence Relations: A Peruvian Case Study - Brioso X. (2017)
This work was partially funded by the Dirección de Gestión de la Investigación at the PUCP, and the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica del Perú (CONCYTEC from its acronym in Spanish), according to the Convenio de Gestión N° 232-2015-FONDECYT. We would also like to thank to Dilmer Dueñas, who kindly participated as instructor in the workshops.